Peningkatan Kualitas Layanan Laboratorium dalam Upaya Meningkatkan Kepuasan Pasien di Puskesmas Awal Terusan Kecamatan SP Padang Kabupaten Ogan Komering Ilir - Ajeng Rifnida Husmi; Nugi Nurdin; Sri Utari (Jurnal Pengabdian Ilmu Kesehatan, 2025)
Laboratory services are an essential part of primary health care in community health centers (puskesmas). High-quality services support accurate diagnosis, timely treatment, and public trust. However, the 2024 community satisfaction survey indicated that the laboratory services at Puskesmas Awal Terusan still face several challenges, particularly in service speed and responsiveness to complaints. This study aims to analyze the quality of laboratory services from the perspective of service users and its relationship with patient satisfaction. The research used a quantitative approach with a cross-sectional design. Data were collected through questionnaires from 98 respondents who had used the laboratory services and were analyzed using descriptive and bivariate analyses (Chi-Square test and simple logistic regression). The results showed that, in general, the quality of services was rated as good, especially in terms of staff empathy, accuracy of results, and implementation of occupational safety. However, there were limitations in equipment availability, long waiting times for results, and low responsiveness to patient complaints, with the indicator “Handling of Complaints, Suggestions, and Feedback” receiving the lowest score in the survey. It can be concluded that the quality of laboratory services at Puskesmas Awal Terusan is generally good but still not optimal. Improvements in staff competence, equipment availability, and the complaint-handling system are needed to enhance patient satisfaction.